Pengembangan Prototipe Aplikasi Berbasis Blockchain dan QR Code dengan Metode ABCDE untuk Rantai Pasok Beras - Barlianto, Agus; Hermadi, Irman; Wahjuni, Sri (Sekolah Sains Data, Matematika, dan Informatika. Institut Pertanian Bogor, 2024)
The development of blockchain-based applications has the potential to revolutionize transparency and traceability in supply chains. This paper presents the development of Ricetrack, a blockchain and QR Code-based application designed to enhance transparency and traceability in the rice supply chain. Ricetrack was developed using Hyperledger Sawtooth technology with the Agile Blockchain DApp Engineering methodology. The application was prototyped and tested in the rice supply chain at Menata Citra Selaras, Bekasi Regency, Indonesia. Before Ricetrack, traceability and data transparency were very minimal or almost nonexistent, with records maintained manually using paper and/or Microsoft Excel. Prototype testing showed significant improvements in traceability, data transparency, and operational efficiency. Key findings include increased ability to track rice from farmers to consumers, enhanced real-time data access for stakeholders, and reduced errors and time in data recording processes. This study offers valuable insights into the practical challenges and benefits of applying blockchain technology in supply chain management and provides a foundation for further improvement and wider implementation of Ricetrack in the future.